Effect of graphene film on laser textured alumina surface characteristics. Issue 2 (1st February 2017) - Yilbas, B.S.; Ibrahim, A.; Ali, H.; Khaled, M.; Laoui, T.
Abstract: Laser gas assisted texturing of alumina surface is considered and the effects of graphene film on the properties of the textured surface are examined. Since laser texturing under the high pressure nitrogen gas jet environments results in formation of aluminum nitride compounds, free energy of the textured surface reduces considerably. The mismatch between the surface free energies of the graphene film and the laser textured surface makes it difficult to transfer the graphene film on the textured surface without rippling and edge defects. A graphene oxide film is formed at the textured surface prior to transferring of the graphene film. The characteristics of the laser textured and the graphene transferred surfaces are assessed using the analytical tools including electron and atomic force microscopes, Raman spectroscopy, X-ray diffraction, and UV visible absorbance spectroscopy. Surface hydrophobicity of the graphene transferred and laser textured surfaces is determined incorporating the water droplet contact angle measurement technique. Friction coefficient of the graphene transferred and laser textured surfaces are measured using the scratch tester. It is found that laser texturing results in hydrophobic characteristics because of the micro/nano size pillars formed at the surface and reduced surface energy due to aluminum nitride compounds. Transferring of the graphene film on to the laser textured surface reduces both the water droplet contact angle and the contact angle hysteresis. The presence of the graphene film reduces the friction coefficient and it does not alter notably the absorption characteristics of the laser textured surface.